Quantitative Analysis of Basalt Damage Under Microwave Radiation Utilizing Uniaxial Compression and Nuclear Magnetic Resonance (NMR) Experiments - Tubing Yin; Jihao Wang; Jiexin Ma; Jianfei Lu; Hao Dai (Applied Sciences)
Microwave-assisted rock breaking is recognized as an effective technology for reducing tool wear and enhancing rock-breaking efficiency. In this study, basalt rock was irradiated with a microwave power of 3 kW and 6 kW for 30 s, 60 s, 90 s, and 120 s. Subsequently, uniaxial compression, uniaxial loading and unloading, and acoustic emission tests were performed. The damage evolution of basalt was assessed through non-destructive acoustic testing methods and nuclear magnetic resonance (NMR) techniques. The results showed that the P-wave velocity, uniaxial compressive strength (UCS), and modulus of elasticity (E) exhibited varying degrees of deterioration as the microwave radiation time increased. An increase in microwave radiation time and power led to heightened acoustic emission activity in basalt and a significant rise in the proportion of shear cracks during uniaxial compression. From an energy perspective, microwave irradiation decreased the energy storage capacity of the basalt specimen prior to its peak point, with increased power and duration. At a microscopic level, porosity and the macroporous fractal dimension increased with extended microwave radiation time and power, indicating that microwave irradiation facilitated the growth of larger fractal pore structures. The findings of this study offer scientific insights for the application of microwave-assisted rock crushing.